Isolation and Characterization of High‐Molecular‐Weight (HMW) Gliadins from Wheat Flour. Issue 6 (1st June 2016) - Schmid, Markus; Wieser, Herbert; Koehler, Peter
Abstract : The aim of this study was to isolate high‐molecular‐weight (HMW) gliadins from wheat flour and to characterize the protein components that contribute to HMW gliadins. Wheat flour Akteur was extracted with a modified Osborne procedure, and the fraction soluble in 60% ethanol (total gliadins) was separated by gel‐permeation HPLC, yielding three fractions, GP1–GP3. GP1 (21.5%) consisted of oligomeric HMW gliadins, GP2 (15.2%) of ω5‐gliadins, and GP3 (63.3%) of ω1, 2‐, α‐, and γ‐gliadins. Two‐dimensional SDS‐PAGE of HMW gliadins showed that interchain disulfide bonds were present in HMW gliadins. The molecular mass distribution of HMW gliadins determined by gel‐permeation HPLC was in a range from 66, 000 to 680, 000 with an average degree of polymerization of 13. Reduced HMW gliadins were further separated by preparative reversed‐phase HPLC into four subfractions (RP1, RP2, RP3, and RP4), which were characterized by SDS‐PAGE and semiquantitative N‐terminal sequencing. HMW gliadins of the wheat flour Akteur contained all types of gluten proteins: 48% low‐molecular‐weight glutenin subunits, 18% γ‐gliadins, 13% α‐gliadins, 9% ω1, 2‐gliadins, 8% HMW glutenin subunits, and 4% ω5‐gliadins. We postulate that the existence of HMW gliadins can be explained by the presence of terminators, which interrupt the polymerization of glutenin subunits during biosynthesis and lead to polymers of limited size (oligomers) that are still soluble in aqueous ethanol.